The potential mechanisms underlying phthalate-induced hypospadias: a systematic review of rodent model studies - Zhang, Youtian; Wang, Jian; Yang, Hongchao; Guan, Yong (Frontiers in Endocrinology, 2024)
Objectives: Maternal exposure to environmental endocrine disruptors, such as phthalates, during pregnancy is a significant risk factor for the development of hypospadias. By consolidating existing research on the mechanisms by which phthalates induce hypospadias in rodent models, this systematic review aims to organize and analyze the discovered mechanisms and their potential connections.The study involved all articles that explored the mechanisms of phthalate-induced hypospadias using rodent models. A comprehensive search of the PubMed and Web of Science databases was conducted using the terms "hypospadias" and "phthalates" before January 20, 2024.Then, two investigators screened for studies worthy of inclusion by setting inclusion and exclusion criteria.Results: Of the initial 326 search results, 22 were included in the subsequent analysis. Based on the commonalities among different results, the mechanisms of phthalate-induced hypospadias could be categorized into the following five groups: sex steroids-related signaling pathways (n=10), epithelialmesenchymal transition (n=6), autophagy (n=5), apoptosis (n=4) and angiogenesis (n=2). Among these, sex steroids-related signaling pathways might serve as a central regulator among all mechanisms, and reactive oxygen species (ROS) also played an important mediating role.The systematic review indicates that phthalates may initially disrupt the balance of sex steroids-related pathways, leading to abnormally elevated levels of ROS and subsequently to other functional abnormalities, ultimately resulting in the development of hypospadias. All these findings